PENINGKATAN KEINOVATIFAN GURU MELALUI PENGUATAN KOMPETENSI PEDAGOGIK DAN LEARNING ORGANIZATION - Dedi Usmayadi; Soewarto Hardhienata; Nandang Hidayat (JURNAL MANAJEMEN PENDIDIKAN, 2020)
IMPROVING TEACHER INNOVATIVITY THROUGH STRENGTHENING PEDAGOGIC COMPETENCIES AND LEARNING ORGANIZATIONSThis study is intended to determine how teachers’ innovativeness can be improved by examining the relationship between teacher innovativeness with pedagogical competency variables and learning organizations The study was conducted using correlational statistical methods to determine whether pedagogical competency variables and learning organization have a positive relationship with teacher innovation. Based on these results, an analysis is then performed using the Sitorem Method to derive recommendations and determining the order of priority improvements that need to be implemented. The study was conducted to the government official teachers of  State Vocational School located in Bogor Regency where the total study population was 184 and the sample taken was 126 teachers. The results showed  that there was a positive relationship between pedagogical competence and teacher innovativeness where the relationship strength ry1 = 0.7655 and there was a positive relationship between learning organization and teacher innovativeness where the relationship strength ry2 = 0.2671. This proved that teacher innovation might be improved through strengthening the  pedagogical competencies and learning organizations.